ANALISIS FRASA TEKS CERITA PENDEK KARYA SISWA KELAS XI SMK NEGERI 1 PADANG PANJANG - Siska, Siska; Tamsin, Andria Catri (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research is to describe the wrong type of phrases in the short story text, describe the causes of phrase errors in the short story text, describe the pattern of revision of the short story text written by student of 11th grade SMKN 1 Padang Panjang. This type of research is a qualitative research with descriptive methods. The instrument of this research is the research itself. This research data is in the wrong phrase. The data source of this research is a short story text written by a student of 11th grade SMKN 1 Padang Panjang. The research data was collected using documentation. Based on the results of the study obtained data as follows. First, the wrong type of phrase in the students' short story text. The wrong type of phrases in the short story texts of students in this study are endocentric phrases and exocentric phrases. Second, the cause of phrase errors in the students' short story text in the form of front-word phrases, mismanagement, wrong due to excessive, the addition of certain words to phrases whose elements are inseparable, and the omission of certain words that connect parts of phrases. third, the pattern of revising the short story text by selecting the language corpus, recognizing errors in the corpus, classifying errors, explaining errors, and evaluating errors. Â Kata kunci:Â Frasa, Kualitatif, Teks Cerita Pendek